True believers : a novel - Andersen, Kurt, 1954- (Random House, 2012)
Karen Hollander is a celebrated attorney who recently removed herself from consideration for appointment to the U.S. Supreme Court. Her reasons have their roots in 1968, an episode she's managed to keep secret for more than forty years. Now, with the imminent publication of her memoir, she's about to let the world in on that shocking secret, as soon as she can track down the answers to a few crucial last questions.